Threatening thresholds?: The effect of disastrous regime shifts on the non-cooperative use of environmental goods and services - Diekert, Florian (Journal of public economics, 2017)
This paper presents a tractable dynamic game in which agents jointly use a resource. The resource replenishes fully but collapses irreversibly if the total use exceeds a threshold. The threshold is assumed to be constant, but its location may be unknown. Consequently, an experiment to increase the level of safe resource use will only reveal whether the threshold has been crossed or not. If the consequence of crossing the threshold is disastrous (i.e., independent of how far the threshold has been exceeded), it is individually and socially optimal to update beliefs about the threshold's location at most once. The threat of a disastrous regime thereby facilitates coordination on a “cautious equilibrium”. If the initial safe level is sufficiently valuable, the equilibrium implies no experimentation and coincides with the first-best resource use. The less valuable the initial safe value, the more the agents will experiment. For sufficiently low initial values, immediate depletion of the resource is the only equilibrium. When the regime shift is not disastrous, but the damage depends on how far threshold has been exceeded, experimentation may be gradual.